2019
DOI: 10.1093/ajcn/nqz071
|View full text |Cite
|
Sign up to set email alerts
|

When poorly conducted systematic reviews and meta-analyses can mislead: a critical appraisal and update of systematic reviews and meta-analyses examining the effects of probiotics in the treatment of functional constipation in children

Abstract: Background Recent systematic reviews and meta-analyses on the efficacy of probiotics in the treatment of functional constipation in children have yielded conflicting results. Objectives The aim of this study was to critically review and update the evidence in this field by mapping all the steps involved against those reported in previous reviews, in an attempt to understand the nature of their conflicting results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 56 publications
1
22
2
1
Order By: Relevance
“…This aligns with previous results, with this term ranking second as a term misunderstood by dietitians in a similar study . This pattern of results are of interest given the rapid increase in the publication of both SRs and meta‐analyses, as well as continuing concern regarding the quality of many of these analyses . These results highlight the need for opportunities for training and mentoring for those conducting SRs, including a specific focus on meta‐analyses, to improve confidence in interpreting results, and ensure SRs produced in the field of nutrition are of high methodological quality.…”
Section: Discussionsupporting
confidence: 83%
“…This aligns with previous results, with this term ranking second as a term misunderstood by dietitians in a similar study . This pattern of results are of interest given the rapid increase in the publication of both SRs and meta‐analyses, as well as continuing concern regarding the quality of many of these analyses . These results highlight the need for opportunities for training and mentoring for those conducting SRs, including a specific focus on meta‐analyses, to improve confidence in interpreting results, and ensure SRs produced in the field of nutrition are of high methodological quality.…”
Section: Discussionsupporting
confidence: 83%
“…Only one RCT showed significant improvement in stool frequency and consistency, and reduction in abdominal pain using Lactobacillus casei rhamnosus Lcr35 (64), however, these findings were contradicted by a later trial (65), and the pooled results of the two RCTs showed no statistical significance for treatment success (66). Previous systematic reviews (66)(67)(68)(69) have also demonstrated insufficient evidence to recommend the use of prebiotics, probiotics, or synbiotics in the treatment of childhood FC, and highlighted important inconsistencies and methodologic errors in prior systematic reviews (70). Table 2 depicts the characteristics of studies assessing the effects of probiotics on children with constipation.…”
Section: Microbiota-based Treatments and Functional Constipation In Cmentioning
confidence: 99%
“…33 A combined high dose of PEG with sodium picosulphate shortens the time needed 34 ( 38 Targeting treatments for the dysbiosis of constipation by probiotics, prebiotics, antibiotics have been popular and have been evaluated in a number of trials. However, the current evidence does not support the use of probiotics as a single or coadjuvant therapy in the treatment of constipation [39][40][41] Recently 'faecal microbiota transplant' has been introduced in adults as a new and promising therapeutic option.42 However, there is no data in children and it is not recommended at present. • Prucalopride a highly specific 5-HT4 receptor agonist with enterokinetic properties and has been found to safe to use in children with FC.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Probiotics have no significant effect on treatment success rate compared with placebo. Probiotic supplementation might result in reduced frequency of glycerin enema use and abdominal pain Harris et al 41 17 RCTs n = 965…”
Section: Approachmentioning
confidence: 99%